The Cleavage and Polyadenylation Specificity Factor in Xenopus laevis Oocytes Is a Cytoplasmic Factor Involved in Regulated Polyadenylation - Dickson, Kirsten S. (American Society for Microbiology, 1999)
During early development, specific mRNAs receive poly(A) in the cytoplasm. This cytoplasmic polyadenylation reaction correlates with, and in some cases causes, translational stimulation. Previously, it was suggested that a factor similar to the multisubunit nuclear cleavage and polyadenylation specificity factor (CPSF) played a role in cytoplasmic polyadenylation. A cDNA encoding a cytoplasmic form of the 100-kDa subunit of Xenopus laevis CPSF has now been isolated. The protein product is 91% identical at the amino acid sequence level to nuclear CPSF isolated from Bos taurus thymus. This report provides three lines of evidence that implicate the X. laevis homologue of the 100-kDa subunit of CPSF in the cytoplasmic polyadenylation reaction. First, the protein is predominantly localized to the cytoplasm of X. laevis oocytes. Second, the 100-kDa subunit of X. laevis CPSF forms a specific complex with RNAs that contain both a cytoplasmic polyadenylation element (CPE) and the polyadenylation element AAUAAA. Third, immunodepletion of the 100-kDa subunit of X. laevis CPSF reduces CPE-specific polyadenylation in vitro. Further support for a cytoplasmic form of CPSF comes from evidence that a putative homologue of the 30-kDa subunit of nuclear CPSF is also localized to the cytoplasm of X. laevis oocytes. Overexpression of influenza virus NS1 protein, which inhibits nuclear polyadenylation through an interaction with the 30-kDa subunit of nuclear CPSF, prevents cytoplasmic polyadenylation, suggesting that the cytoplasmic X. laevis form of the 30-kDa subunit of CPSF is involved in this reaction. Together, these results indicate that a distinct, cytoplasmic form of CPSF is an integral component of the cytoplasmic polyadenylation machinery.